(untitled) (Research, Society and Development, 2023)
Angiogenesis is the production of capillaries through new, existing blood vessels. Being part of the normal process of the human body, it plays a very im- portant role in the physiological order, such as tissue regeneration, and is also linked to the development of numerous pathologies, including, for example, of tu- mor growth. The study aims to characterize the factors that lead to the decline of solid-type malignant tumors in people with Down syndrome linked to angiogenesis or the formation of new vessels in the feed of these tumors. To this end, a qualita- tive-qualitative study was carried out through a systematic literature review using the prism method. Two online databases were used: National Library of Medicine (PubMed), Scientific Electronic Liberay Online (SciELO), which will be chosen using the Health Sciences descriptors (DECS). The RCAN1 (Down Syndrome Critical Region 1) gene plays an important role in regulating angiogenesis, a process by which new blood vessels are formed from existing ones. Overexpression of the RCAN1 (Down Chromosome Region 1) gene, located on chromosome 21, results in the excessive production of a protein that inhibits the activity of calcineurin, an enzyme critical in the regulation of several cellular pathways, including the NFAT (Factor Nuclear Activation of T Cells), which plays an essential role in the develop- ment of tumors. Understanding the precise switches by which the RCAN1 gene interacts with angiogenesis could pave the way for the development of therapies aimed at reducing solid tumors.